The title as a constituent and structural component of T. G. Shevchenko's poetic works: general characteristics, specifics - Alla Ruban (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The author of the article focuses on the paratextuality of "Kobzar" by T G. Shevchenko, particularly, on the relationship between the poetic texts of the collection and the titles. There made an attempt to classify the titles of the works from different positions.